Effects of surfactants on the properties of epoxy/graphene nanocomposites. (July 2018) - Wei, Jiacheng; Saharudin, Mohd Shahneel; Vo, Thuc; Inam, Fawad
Recently, graphene has attracted extensive research interests due to its superior mechanical, electrical and thermal performance. Small loadings of graphene can increase the properties of epoxy significantly. However, because of the large surface area of graphene, it is a challenge to disperse graphene in liquid epoxy. Strong van der Waals force causes reaggregation of graphene in the matrix. As commonly used surfactants, sodium dodecyl sulphate and gum arabic have been used a lot to de-bundle graphene, however, their dispersing efficiencies for graphene in epoxy matrix is unknown. Therefore, to evaluate their dispersing efficiencies, epoxy/graphene nanocomposites had been made and mechanical properties, dynamic mechanical analysis, thermal gravimetric analysis and scanning electron microscopy tests of nanocomposites had been conducted. The results show that the properties of nanocomposites had been enhanced largely after using sodium dodecyl sulphate and gum arabic. Sodium dodecyl sulphate shows higher dispersing effectiveness than gum arabic.